Exploring Customer Satisfaction: Mediation Role in Repurchase Intention of Tofu MSMEs - Abda'u, Rizqy; Ayuanti, Rafikhein Novia; Saputra, Beny Mahyudi (IQTISHODUNA, 2025)
The purpose of this study is to analyze the influence of customer experience, customer value, and price perception on repurchase intention in tofu MSMEs in Tofu Village Kediri City, using customer satisfaction as a mediating variable. A quantitative approach was employed in this study, along with Structural Equation Modeling-Partial Least Squares (SEM-PLS) as the analytical method. Data were collected using an online questionnaire with a 5-point Likert scale, involving 150 respondents selected through purposive sampling. The results of the study indicate that customer experience, customer value, and price perception positively and significantly affect customer satisfaction and repurchase intention. Customer satisfaction was a mediating variable that strengthened the relationship between the three independent variables and repurchase intention. This research contributes to the literature on consumer behavior in the context of MSMEs, particularly in the tofu industry. It provides insights for business owners to enhance customer satisfaction and encourage repurchase intention through strategies based on customer experience, customer value, and price perception. Future research is recommended to improve discriminant validity for more comprehensive results.